Variation of Pectin and Sugar Concentration on The Characteristic of Passion Fruit Gummy Candy - Anjliany, Meysin; Nabilah, Tri Adelti; Syafutri, Merynda Indriyani (Department of Technology of Agricultural product (THP) Jambi University, 2022)
Gummy candy is a type of soft candy who made from juice and gel-forming materials. The objective of this research was to determine the effect of variation of pectin and sugar concentration on physical and chemical characteristics of passion fruit (Passiflora edulis) gummy candies. The research using factorial completely randomized design with two factors, namely concentration variation of pectin (1%, 1,5%, 2%) and concentration variation of sugar (30%, 40%, 50%). The observed parameters included physical characteristics (color, elasticity) and chemical characteristics (water content, ash content, pH, vitamin C, reducing sugar content, total acid). The result showed that concentration of pectin significantly affected on color (lightness, redness, yellowness), elasticity, water, ash, vitamin C, reducing sugar content, and total acid content, where as concentration of sugar significantly affected on color (lightness, yellowness), elasticity, water, ash, pH, vitamin C, reducing sugar content, and total acid content. The interaction affected significantly on elasticity, water, reducing sugar content, and total acid content. A3B2 treatment (pectin concentration 2% and sugar concentration 40%) was the best treatment based on parameters of water content (17.41%), ash content (1.06%), and reducing sugar content (8.28%).